Effect of thermomechanical treatments on the phases, microstructure, microhardness and young's modulus of ti-25ta-zr alloys - Kuroda, Pedro Akira Bazaglia [UNESP] (2019)
Titanium and its alloys currently are used as implants, possessing excellent mechanical properties (more suited than stainless steel and Co-Cr alloys), good corrosion resistance and good biocompatibility. The titanium alloy used for most biomedical applications is Ti-6Al-4V, however, studies showed that vanadium and aluminum cause allergic reactions in human tissues and neurological disorders. New titanium alloys without the presence of these elements are being studied. The objective of this study was to analyze the influence of thermomechanical treatments, such as hot-rolling, annealing and solution treatment in the structure, microstructure and mechanical properties of the Ti-25Ta-Zr ternary alloy system. The structural and microstructural analyses were performed using X-ray diffraction, as well as optical, scanning and transmission electron microscopy. The mechanical properties were analyzed using microhardness and Young's modulus measurements. The results showed that the structure of the materials and the mechanical properties are influenced by the different thermal treatments: rapid cooling treatments (hot-rolling and solubilization) induced the formation of ff and phases, while the treatments with slow cooling (annealing) induced the formation of martensite phases. Alloys in the hot-rolled and solubilized conditions have better mechanical properties results, such as low elastic modulus, due to retention of the phase in these alloys.